HARMONIZATION OF NATIONAL AND INTERNATIONAL EXPERIENCE REGARDING REGISTERED CAPITAL - STOIKA, Natalia; KOVACH, Antonia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article analyzes the differences in the accounting systems of two neighboring countries, paying particular attention to the registered capital of business entities.Operations related to registered capital are currently regulated by a significant number of regulatory documents. However, these documents contain many inconsistencies from generally accepted international standards. Therefore, one of the priorities is to eliminate existing differences. This is helped by a comparative analysis of the national and international practices. Registered capital plays an important role in the formation of business entities, because it reflects the value contributed by the founders to the registered capital in the form of various economic resources. Because of this, the legislation of Ukraine establishes specific requirements for its formation, such as the size, term of contribution, types of contributions. The article also considered the peculiarities of the accounting of registered capital. Accounts on which operations with registered capital are reflected are the 40 “Registered (share) capital”, which includes the 401 “Registered capital”, and 46 “Unpaid capital”.One of the important partners for Ukraine is Hungary, which is why we made a comparison with it. In Hungary, the laws impose much higher requirements regarding the registered capital for the establishment of business entities. The regulation of the accounting system also differs in the two countries. Although the chart of accounts in Hungary is significantly different and more complicated to use, the registrations of operations with registered capital on accounts do not differ significantly.Based on the comparative analysis, the main differences between the practices of the two countries were highlighted and recommendations were given to the national companies.
Keywords: registered capital; capital; business entity; accounts; accounting system; operations